2022
DOI: 10.1007/s12010-021-03770-y
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Effect of Padina boergesenii on Growth, Immune Response, and Disease Resistance Against Pseudomonas aeruginosa in Cirrhinus mrigala

Abstract: Seaweeds are potential renewable resources in the aquatic environment. The present study was made to evaluate the in uence of seaweed Padina boergesenii incorporated with basal diet in different concentrations. The Phyto-constituents of the seaweeds were characterized by Gas Chromatography Mass Spectrometry. Diets were formulated to include seaweed meal at elevated levels from 0.5%, 2.5%, 4.5% and 6.5%. The C. mrigala fed with P.boergesenii incorporated with basal diet for a period of 45 days. The Growth param… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…In recent years, there has been an increase in interest in algae extraction’s prophylactic abilities against bacterial challenges to aquatic animals. It has been stated that various algae extractions offer resistance to virulent bacteria Aeromonas hydrophila and Edwardsiella tarda in common carp [ 46 ], A. hydrophila in tilapia [ 51 ], A. hydrophila in rainbow trout [ 39 ] and to P. aeruginosa in Cirrhinus mrigala [ 16 ]. Nevertheless, in the literature, there is no study on the resistance of the P. boergesenii -fed Nile tilapia to P. putida .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, there has been an increase in interest in algae extraction’s prophylactic abilities against bacterial challenges to aquatic animals. It has been stated that various algae extractions offer resistance to virulent bacteria Aeromonas hydrophila and Edwardsiella tarda in common carp [ 46 ], A. hydrophila in tilapia [ 51 ], A. hydrophila in rainbow trout [ 39 ] and to P. aeruginosa in Cirrhinus mrigala [ 16 ]. Nevertheless, in the literature, there is no study on the resistance of the P. boergesenii -fed Nile tilapia to P. putida .…”
Section: Discussionmentioning
confidence: 99%
“…The control diet, which served as the basal diet, was not supplemented with P. boergesenii water extract. Feeding rate used in this study was chosen according to the earlier finding in Cirrhinus mrigala [ 16 ] to detect the most suitable concentration of the P. boergesenii water extract powder. Hence, the supplemented diet was prepared by thoroughly mixing the basal diet with 4.5% concentration of P. boergesenii water extract powder until stiff dough was obtained, and water was used as the binding agent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cian et al (2016) reported that chelating peptides obtained from seaweed Pyropia columbina effectively enhance the bioaccessibility of iron. Earlier studies have reported that seaweed signi cantly enhanced the RBC counts, Hb values and/or Hct ratios of L. calcarifer(Zeynali et al, 2020), Cirrhinus mrigala(Ragunath & Ramasubramanian, 2022) and Oreochromis niloticus(Nur et al, 2020;Fredrick Raja et al, 2022). In this study, an increase was observed in the granulocyte ratio and a decrease in the lymphocyte ratio was observed in sh when fed diets supplemented with P6.…”
mentioning
confidence: 98%